2012
DOI: 10.1128/jb.00453-12
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of Two Clinical Isolates of Mycobacterium tuberculosis from Kerala, South India

Abstract: bWe report the annotated genome sequence of two clinical isolates of Mycobacterium tuberculosis isolated from Kerala, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…No RD region was found to be absent in RGTB423 and only RD RIO deletion was detected in RGTB327. Strain RGTB423 has been found to belong to SCG 1 and PGG 1 [ 25 ], but in-silico PCR analysis showed that the strain had the pks15/1 7 bp frameshift deletion and the TbD1 deletion indicative of a modern Euro-American strain [ 23 ]. Nevertheless, this classification is incongruent with the SCG and PGG classification [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…No RD region was found to be absent in RGTB423 and only RD RIO deletion was detected in RGTB327. Strain RGTB423 has been found to belong to SCG 1 and PGG 1 [ 25 ], but in-silico PCR analysis showed that the strain had the pks15/1 7 bp frameshift deletion and the TbD1 deletion indicative of a modern Euro-American strain [ 23 ]. Nevertheless, this classification is incongruent with the SCG and PGG classification [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…S1, some genome sequences, e.g. Mtb_CAS_NITR204, Mtb_Haarlem3_NITR202, Beijing/ NITR203, Mtb_EAI5_NITR206, RGTB423, RGTB327 or Mtb_EAI5 (Madhavilatha et al, 2012;Narayanan and Deshpande, 2013;Al Rashdi et al, 2014) indicate much greater diversity than other related MTBC strains and/or show characteristics that do not match with the phylogenetic groupings suggested by their names and the clustering obtained. The genome sequences of Mtb_EAI5, Mtb_EAI5_NITR206 and RGTB423, for example, cluster with well characterized TbD1-intact L1 M. tuberculosis strains (Fig.…”
Section: Evolution and Age Of M Tuberculosis Senso Strictomentioning
confidence: 89%
“…As shown in http://onlinelibrary.wiley.com/10.1111/mmi.12720/suppinfo, some genome sequences, e.g. Mtb_CAS_NITR204, Mtb_Haarlem3_NITR202, Beijing/NITR203, Mtb_EAI5_NITR206, RGTB423, RGTB327 or Mtb_EAI5 (Madhavilatha et al ., ; Narayanan and Deshpande, ; Al Rashdi et al ., ) indicate much greater diversity than other related MTBC strains and/or show characteristics that do not match with the phylogenetic groupings suggested by their names and the clustering obtained. The genome sequences of Mtb_EAI5, Mtb_EAI5_NITR206 and RGTB423, for example, cluster with well characterized TbD1‐intact L1 M. tuberculosis strains (http://onlinelibrary.wiley.com/doi/10.1111/mmi.12720/suppinfo), but whole genome BLAST searches in GenBank show a TbD1‐deleted locus and several other specific sequence characteristics of the H37Rv M. tuberculosis strain [e.g.…”
Section: Quality Assurance Of M Tuberculosis Genome Sequences Will Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of ancestral strains of Mycobacterium tuberculosis in India has been reported using various genotyping methods (15). The current genotyping methods have low discriminatory power, and whole-genome sequencing of clinical isolates of M. tuberculosis has now become the preferred approach for genotyping these clinical isolates.…”
Section: Genome Announcementmentioning
confidence: 99%